2016
DOI: 10.4103/2278-0513.197871
|View full text |Cite
|
Sign up to set email alerts
|

Profile of molecular subtypes of breast cancer with special reference to triple negative: A study from Northeast India

Abstract: to therapy. Current routine clinical management of BC relies on the availability of robust clinical and pathological prognostic and predictive factors to support patient decision-making in which potentially suitable treatment options are increasingly available. The traditional staging on the basis of tumor size and lymph node status remains the cornerstone of outcome indicators; it has become clear that not all BC s presenting at the same stage have the same underlying biology or clinical behavior. [2] Prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Visual inspection of the funnel plot for these data showed 3 outliers. 18 , 31 , 37 Re-analysis of the pooled data from the remaining 11 studies after removal of the outliers showed a marked decrease in heterogeneity. The pooled OR showed that lymph node positivity was favored in TNBC over non-TNBC (OR, 1.39; 95% CI, 1.21 to 1.60), with a significant overall effect ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Visual inspection of the funnel plot for these data showed 3 outliers. 18 , 31 , 37 Re-analysis of the pooled data from the remaining 11 studies after removal of the outliers showed a marked decrease in heterogeneity. The pooled OR showed that lymph node positivity was favored in TNBC over non-TNBC (OR, 1.39; 95% CI, 1.21 to 1.60), with a significant overall effect ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 98%
“…(B) Comparison of LN-positive incidence after removal of outliers. Funnel plot analysis shows that 3 studies (Gogoi et al, 31 Mukherjee et al, 37 and Agarwal et al 18 ) were outliers of the pooled OR (Data Supplement). These studies were excluded and the pooled OR recomputed.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Gogoi et al, IHC evaluation of breast cancers showed ER+in 40.62%, PR+35.77%, Her2/Neu+18.69%. 14 Azizun-Nisa et al in a study done in Pakistan in 2008 also found similar results with only 32.7% ER and 25.3% PR positivity. 15 This study classified tumours into molecular subtypes based on the protein expression pattern in IHC.…”
Section: Discussionmentioning
confidence: 59%
“…A study done in North India has reported a very similar result where they too had a high prevalence of TNBC [21]. An Indonesian study done in 2014 too, shows a similar distribution of molecular subtypes but with a lesser percentage of TNBC [22].…”
Section: Resultsmentioning
confidence: 84%